The current practice of interfaith child custody disputes in Bangladesh and Malaysia: a comparative analysis - Hassan, Kamrul; Fauzi, Husna (2019)
Interfaith child custody dispute is one of the burning issues in both Bangladesh and Malaysian legal system. Whenever an interfaith couple decided to divorce or leagally separated, conflict as to the custody right of the child is likely to occur. It will eventually lead to socio-legal-religious complications during the trial. The child custody issue is correlated with the wellbeing and welfare of the child of the marriage. The interfaith parents should consider what would be the best interest of their child before applying for divorce or judicial separation. As Bangladesh and Malaysia consist of multireligious and multicultural societies, interfaith child custody disputer adversely impacts on the social and family life. The application of the different set of laws in the existing judicial system seems to be in adequate in resolving interfaith child custody disputes. The aim of this paper is to provide a comparative overview of the existing interfaith child custody disputes in Bangladesh and Malaysia. It seeks to examine the current legal framework and legal disputes in both jurisdiction. This paper is based on theoretical analysis; therefore it adopts the library research, where reference to relevant data from text books, journals, legal provisions and case law relating to the interfaith child custody disputes is made. The study concludes that an adequate legal framework would be the best solution in deciding interfaith child custody disputes.